Interethnic Relations in Russia at the End of the 19th - the Beginning of the 20th Century - E. S. Shavlokhova (Научный диалог, 2017)
The question is raised on interethnic relations in the late 19th - early 20th century in Russia, especially in the ethnic environment of the North Caucasus. It is noted that Russia differed from other countries by the fact that in the new territories it was not looking for sources of raw materials for industrial development and markets. The measures are shown to resolve the conflicts that have inevitably arisen in the areas of compact settlement of several nations. The relevance of the study is determined by the task to provide a reliable and efficient management of the country, occupying a vast territory with a diverse population. Scientific novelty consists in increasing the level of scientific and theoretical understanding of the goals, means and mechanisms of functioning of the Russian system of state management of national regions. The conception of development of the Russian state system of management of small peoples is formulated. This conception is based on well-documented hypothesis that the functioning of the means and mechanisms of influence on the situation in the outlying areas of the state gradually transformed into a policy of strengthening of positions of power in the national regions. The author believes that it is important to show the real situation in the sphere of interethnic relations in the North Caucasus in this period.